Quality Assessment of Clinical Guidelines for Preventing Falls in Hospitalized Elderly People in Iran Using the Appraisal of Guidelines, Research, and Evaluation (AGREE) Checklist - Mahsa Soleimani; Maryam Shirazi; Mahrokh Keshvari (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Hospitalization is a vulnerable period for the elderly. During this period, they are at risk of falling. There are various clinical guidelines for fall prevention, whose usefulness depends on their quality and clinical acceptance. This study was to evaluate the methodological quality of selected clinical guidelines for fall prevention in hospitalized elderly people in Iran using the Appraisal of Guidelines, Research, and Evaluation (AGREE) checklist.  Methods & Materials A systematic search was conducted for clinical guidelines published from 2009 to 2020 using the keywords clinical guideline, falling, prevention, aged, and hospitalization. Of 351 clinical guidelines identified, 4 guidelines were selected based on the inclusion and exclusion criteria and by a purposive sampling method. The quality of the selected guidelines was evaluated by 5 experts independently using the AGREE II checklist. Based on the quality scores, the guidelines were categorized as "highly recommended" or "recommended with modifications".  Results The "Falls Assessment and Prevention of Falls in Older People", "Preventing Falls and Harm From Falls in Older People", and "Preventing Falls and Reducing Injury from Falls" were categorized as highly recommended, while the "Post Fall Multidisciplinary Management Guidelines for Western Australian Health Care Settings" was categorized as "recommended with modifications". Therefore, they can be localized and used to reduce the risk of falls in hospitalized elderly people in Iran. The mean overall scores of 6 domains for the guidelines were as follows: 91. 1% for "clarity of presentation", 86. 6% for "scope and purpose", 83. 6% for "stakeholder involvement" 72. 08% for "editorial independence", 71. 14% for "rigor of development", and 66. 66% for "applicability".  Conclusion Evaluation of the methodological quality of clinical guidelines using the AGREE tool should be done to be able to be used in clinical practice. It is recommended to use these tools in updating the current or future clinical guidelines to ensure their methodological quality.